The Impact of Artificial Intelligence on Public Relations Strategies: A Quantitative Analysis of the Middle East’s 10 Most Valuable Brands - Aguerrebere, Pablo; Khan, Kinza; Abraham, Jessica (International Journal of Communication and Public Relation, 2025)
Purpose: This paper’s research question is: How does artificial intelligence impact the main elements of public relations strategies: communication objectives, target audiences, brand positioning, and creative concepts (art and message)? Methodology: To answer this question, we conducted a literature review about how this technology impacts the marketing industry, branding campaigns, and public relations strategies. Then, we resorted to Brand Finance’s “Middle East 150” report and defined 20 indicators to quantitively analyze how the Middle East’s 10 most valuable brands used artificial intelligence to enhance their public relations strategies. Findings: Our results revealed that the three most respected indicators were the use of several target audiences simultaneously (78), impactful images (74), and storytelling (73). The brands respecting the most criteria were Sabic and Stc. Unique Contribution to Theory, Practice and Policy: Companies must use this technology to revisit the public relations profession and implement more credible branding models based on sharing meaningful content that improves stakeholders’ lives. We recommend brands to integrate artificial intelligence professionally into their public relations departments, recruit experts in this area, update their communication plans, and implement new internal practices and indicators guiding public relations campaigns.